Assistance In Optimizing Fishery Processing Technology And Protection Of Intellectual Property Rights For Pokdakan Sakato Farm In Supporting The Creative Economy - WULANDARI, RATIH AGUSTIN; Ermawati, Eka; Suryana, Febriyanno; Efendi, Raimon (Unpad Press, 2025)
in rural areas. Pokdakan Sakato Farm, a catfish farming group in Dharmasraya Regency, faces various challenges, including price fluctuations, inconsistent fish sizes at harvest, limited processing technology, lack of product legality, and underutilized digital marketing. This community service program aims to enhance the added value of aquaculture products through the optimization of processing technology, digital marketing strategies, and legal assistance for product certification. The program was implemented through several stages, including observation, training, technology application, and evaluation. The outcomes indicate improved technical skills among members, product diversification such as smoked catfish and seasoned catfish, increased production efficiency, the development of digital marketing systems, and the initiation of product legalization processes. The program also fostered institutional awareness for professional and sustainable business management. Further actions include continuous mentoring, follow-up training, and strategic collaboration with government agencies to ensure sustainability and competitiveness of Pokdakan Sakato Farm's business